2010
DOI: 10.1002/eji.200939251
|View full text |Cite
|
Sign up to set email alerts
|

Continuous CD27 triggering in vivo strongly reduces NK cell numbers

Abstract: NK cells are important mediators of the early defense. In mice, immature and mature NK (mNK) cells constitutively express the TNF receptor family member CD27; however, mNK cells eventually lose CD27 expression and become resting NK cells. Interaction of CD27 with its ligand, CD70, enhances proliferation and effector functions of NK cells. We used mice that constitutively express CD70 on B cells (CD70-Tg) to study the in vivo effects of continuous triggering of CD27 on NK cells. Continuous CD70-CD27 interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…These features made it difficult to determine whether or not both effector functions were performed by the same NK cell subset. This is consistent with the results of De Colvenaer et al, who reported that continuous CD27 triggering in vivo resulted in strongly downmodulated CD27 expression on NK cells and in a severe reduction in NK cell numbers (12). Our results that showed downregulation of CD27 expression on NK cells and a decrease in NK cell percentages after DNA-based immunization indirectly confirm their activation state.…”
Section: Cd27supporting
confidence: 93%
“…These features made it difficult to determine whether or not both effector functions were performed by the same NK cell subset. This is consistent with the results of De Colvenaer et al, who reported that continuous CD27 triggering in vivo resulted in strongly downmodulated CD27 expression on NK cells and in a severe reduction in NK cell numbers (12). Our results that showed downregulation of CD27 expression on NK cells and a decrease in NK cell percentages after DNA-based immunization indirectly confirm their activation state.…”
Section: Cd27supporting
confidence: 93%
“…20 NK cell numbers are strongly reduced in these mice, and the remaining NK cells produce less IFN-␥ than wild-type (WT) mice. 21 Here we describe that CD27-mediated T-cell activation has a strong and specific impact on myelopoiesis, as CD70TG mice are almost devoid of eosinophils, whereas the formation of neutrophils and monocytes is actually increased. Detailed analysis revealed that this defect in eosinophil formation can be fully attributed to the increased production of IFN-␥ by effector T cells in these mice.…”
Section: Introductionmentioning
confidence: 77%
“…10 Consequently, these CD70-transgenic (CD70TG) mice display improved T-cell immunity and efficiently counter a challenge with influenza virus or tumor cells. 11 However, the increased pool of effector T cells also seriously disrupts the hematopoietic system at different levels, as CD70TG mice gradually lose their B cells 10 and eosinophilic granulocytes 12 because of chronic exposure to IFN-␥, lose their NK cells, 13 and eventually even exhaust their naive T-cell pool. 14 Here we describe that CD70TG mice also become anemic, which is fully dependent on the production of IFN-␥.…”
Section: Introductionmentioning
confidence: 99%